2014
DOI: 10.1098/rspb.2014.1137
|View full text |Cite
|
Sign up to set email alerts
|

A texture-processing model of the ‘visual sense of number’

Abstract: It has been suggested that numerosity is an elementary quality of perception, similar to colour. If so (and despite considerable investigation), its mechanism remains unknown. Here, we show that observers require on average a massive difference of approximately 40% to detect a change in the number of objects that vary irrelevantly in blur, contrast and spatial separation, and that some naive observers require even more than this. We suggest that relative numerosity is a type of texture discrimination and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 41 publications
9
108
2
Order By: Relevance
“…According to the energy-based models of Dakin and collaborators (e.g. Dakin et al, 2011;Morgan et al, 2014), these patterns should appear more numerous than those with isolated dots. Figure 2 shows psychometric functions for the tasks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the energy-based models of Dakin and collaborators (e.g. Dakin et al, 2011;Morgan et al, 2014), these patterns should appear more numerous than those with isolated dots. Figure 2 shows psychometric functions for the tasks.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Stoianov and Zorzi (2012) have shown that number (rather than density) emerges spontaneously within an unsupervised learning algorithm. If numerosity were a sensory by-product of density and area, as suggested by several research groups (Dakin, Tibber, Greenwood, Kingdom, & Morgan, 2011;Durgin, 2008;Morgan, Raphael, Tibber, & Dakin, 2014;Tibber, Greenwood, & Dakin, 2012;Tibber et al, 2013), sensitivity for numerosity should be predictable from the independent measures of area and density. We recently directly tested this hypothesis and showed that when subjects discriminate items varying in the space spanned by number, density and area, discrimination thresholds are far lower for number than for density of area, suggesting that number rather than density is sensed spontaneously .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, the retinotopic feature of numerosity adaptation would make it difficult to use IPS as a candidate because IPS represents numerosity quite abstractly, independently of whether the objects are distributed in space or time and independently of modality (Butterworth, 2008). In fact, it is not easy to find compelling reason to accept the idea that numerosity is an elementary quality of perception, similar to color or other primary features (Morgan, Raphael, Tibber & Dakin, 2014;Raphael & Morgan, 2015). Numerosity cognition is proposed to be accompanied by processes for a combination of surrogate features (Franconeri, Bemis, & Alvarez, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to this approach, numerosity is a principal feature of our environment that can be directly sensed, comparable to color, contrast, or brightness. A concurrent model proposes that numerosity is derived indirectly from non-numerical stimulus dimension such as density, for example (Morgan, Raphael, Tibber, & Dakin, 2014; see also Gevers, Cohen Kadosh, & Gebuis, 2016). …”
Section: Numbers and Spacementioning
confidence: 99%